Regulation of the Invasive Plant Heracleum persicum by Private Landowners in Tromsø, Norway. (8th June 2017) - Meier, Sophie; Taff, Gregory N.; Aune, Jens B.; Eiter, Sebastian
Abstract : In the city of Tromsø in northern Norway, invasive Tromsø palm (Norwegian: Tromsøpalme; English: Persian hogweed) is widespread. Although Tromsø palm has negative impacts on biodiversity and contains a phototoxic sap that burns human skin, it is also considered to be a local symbol of Tromsø city and is appreciated by many inhabitants. This study examined private landowners' characteristics, perceptions, and landowners' regulation of invasive Tromsø palm on their parcels on Tromsø Island in 2012 (vegetation season: May–September) to provide information concerning which landowner groups could be assisted by official regulation. Eleven key informants and 17 landowners were interviewed. Afterward, Tromsø palm on Tromsø Island was mapped using aerial photos and street-level photos from Google Maps ® /Google Street View ® and fieldwork verification. This distribution map was superimposed on a property map in a geographic information system to produce a map showing private parcels that contained Tromsø palm and associated neighboring parcels that did not contain Tromsø palm. Questionnaires were mailed to the 441 owners of the selected parcels, and 199 of the returned questionnaires were analyzed. Tromsø palm was more likely to be fully regulated/absent on a parcel that was inhabited (particularly if the owner lived on-site) and less likely to be fully regulated/absent if the parcel was jointly managed by several households. These findings indicate that authorities could focus their management efforts on supporting regulation efforts of those private landowners who own currently uninhabited or rented-out parcels and landowners of parcels jointly managed by several households. Furthermore, those landowners who found regulation measures against the plant on Tromsø Island important tended to have partly or fully regulated Tromsø palm on their plots. This might imply that information campaigns from authorities might encourage more landowners to regulate Tromsø palm.